External quality assessment scheme for HbA1c assays in Thailand: A 5-year experience - Supaporn Suparak (2022)
Background: Thailand National External Quality Assessment Scheme (NEQAS) for HbA1c was established to evaluate the quality of HbA1c assays in Thailand in 2016. Methods: HbA1c results from participating laboratories were compared to the target value assigned by the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference system. Results: The pass rates of participating laboratories during 2016–2020 were72–88%. The mean bias ranged between −0.19 and 0.20% of HbA1c. SD ranged from 0.30 to 1.08% of HbA1c. The overall coefficients of variation ranged from 4.46-15.66%. Conclusions: Performance evaluation using IFCC assigned values indicated that different assay methods had an effect on HbA1c results. Participation in external quality assessment programs for HbA1c analysis is essential for improving laboratory quality and benefiting patient management.